2012
DOI: 10.3177/jnsv.58.408
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Improves Insulin-Stimulated Akt Phosphorylation in Liver and Skeletal Muscle in Diabetic KK-Ay Mice

Abstract: Abbreviations: GLUT4, glucose transporter 4; IL-6, interleukin 6; IR, insulin receptor; IRS-1, insulin receptor substrate-1; MCP-1, monocyte chemoattractant protein-1; PI3K, phosphatidylinositol 3-kinase; TNF-a, tumor necrosis factor a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…The mechanism of this effect is not yet clear but could be a result of improved glucose uptake by skeletal muscle or up-regulation of insulin sensitizing hormones such as adiponectin [17], [20]. Though irisin is secreted in response to exercise, another state of increased energy expenditure, we did not detect a statistically significant change in irisin levels after eight weeks of coffee consumption [8].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The mechanism of this effect is not yet clear but could be a result of improved glucose uptake by skeletal muscle or up-regulation of insulin sensitizing hormones such as adiponectin [17], [20]. Though irisin is secreted in response to exercise, another state of increased energy expenditure, we did not detect a statistically significant change in irisin levels after eight weeks of coffee consumption [8].…”
Section: Discussioncontrasting
confidence: 56%
“…One proposed mechanism to explain this association is that coffee may facilitate glucose uptake by skeletal muscle via increased translocation of the GLUT4 transporter to the plasma membrane [17][19]. Also, coffee consumption has been associated with increased levels of adiponectin, a hormone thought to have insulin-sensitizing properties [20][22].…”
Section: Introductionmentioning
confidence: 99%
“…In C57BL/6J mice fed a high-fat diet, coffee ingestion also improved insulin sensitivity (4). Furthermore, we found that coffee increased the activation of Akt in insulin signaling in the liver and skeletal muscle (5). Insulin resistance and impaired insulin secretion are associated with the development of type 2 diabetes.…”
mentioning
confidence: 70%
“…Giani and others proved that high‐fructose diet caused a significant reduction of insulin sensitivity and p85‐PI3K expression in the skeletal muscle of rats (Giani and others ). Kobayashi and others proved that the phosphorylation of serine in PKB could improve insulin sensitivity and glucose uptake in skeletal muscle of diabetic KKAy mice (Kobayashi and others ). In CHS‐treated mice, insulin‐induced phosphorylation of p‐85‐PI3K, Ser473‐PKB, and Thr308‐PKB was upregulated in comparison to those in HFSD mice.…”
Section: Discussionmentioning
confidence: 99%